Las formas de resistencia ante la violencia en Perra brava de Orfa Alarcón (Altre Modernità, 2019)
In Perra brava, the axis of the story revolves around the metamorphosis of the heroine, who becomes intimidated and abused as a ferocious and ruthless victimizer. In a wide range of emotions related to violence, the protagonist goes from terror and fear passing through the astonishment, until reaching the opposite pole represented by admiration and fascination for the violent. Orfa Alarcón weaves intrafamily violence with the physical and emotional abuse that Julio exerts on Fernanda, as if between one period of his life there was no escape, accentuated, with childhood memory, the feelings of vulnerability, dependence and despair of the protagonist. In this process of progressive degradation, the different forms of violence that plague Mexican society deriving from the presence of narcotics are shown with harshness and, in turn, present the forms of resistance of these beings who struggle to survive in a world where the existence of neoliberal discourses seems to condemn them to a sinister destiny. In this work we intend to analyze this process of transformation, of degradation of Fernanda's character, as a form of resistance to the violence of which she is the object and how she becomes a “brave bitch”, in order to impose herself in a violent and corrupt society. the one that has been continuous subject of vexation and outrage.